What is good communication for people living with dementia? A mixed-methods systematic review. (31st July 2017) - Alsawy, Sarah; Mansell, Warren; McEvoy, Phil; Tai, Sara
ABSTRACT: Background: Many strategies have been recommended to support caregivers in communicating with people who live with dementia. However, less is known about what makes communication a good and meaningful experience from the perspective of people with dementia. Understanding this may enhance the person with dementia's sense of connectedness, strengthen their relationships, and facilitate person-centered care. The current review aimed to evaluate research that examined experiences of communication in people living with dementia. Studies that examined reports provided by people with dementia, healthcare professionals, and family caregivers were included. Methods: A mixed-methods systematic review was conducted using PsychINFO, MEDLINE, and EMBASE databases. Results: After applying the eligibility criteria, 15 studies were included. Although eight of these recruited people with dementia, only one focused on their perspectives of communication experiences and the remaining studies focused on the perspectives of family caregivers and healthcare professionals. These studies either explored experiences without suggestions of communication methods, "open exploration, " or through examining experiences of strategies, "exploration of strategies." A significant theme was around communication difficulties that affected interpersonal relationships and activities of daily living. Conversely, personhood strategies and a strong underlying relationship were believed to facilitate communication. The one study that examined the perspectives of people with dementia emphasized the importance of retaining valued relationships and feeling respected during communication. Conclusions: The need to involve people with dementia in research, particularly around their experiences of communication, is evident. Such research would be imperative for facilitating person-centered care, strengthening social relationships, and informing training programs.